1191 The Use of CT Urography to Diagnose Upper Tract Urothelial Carcinomas (UTUC); Managing Surgical Resources During The COVID-19 Pandemic. (12th October 2021) - Wong, S; Sehgal, R; Birks, T; Allen, D; Goyal, A; Kucheria, R; Ajayi, L; Ellis, G
Abstract: Introduction: Upper tract urothelial carcinomas (UTUC) account for 5-10% of urothelial malignancies. Rapid diagnosis is essential as 60% are invasive at diagnosis and confer poor prognoses. European Association of Urology (EAU) guidelines recommend CT urography (CTU) for initial diagnosis and staging of UTUCs. Diagnostic ureteroscopy (URS) is used second line where diagnosis is unclear. The COVID-19 pandemic has limited theatre access and may delay diagnosis of suspected UTUC. Our aim was to evaluate specific CTU findings in predicting UTUC to aid prompt diagnosis and risk stratification in a tertiary centre. Method: A retrospective analysis was performed on 122 patients who underwent CTU with diagnostic URS over two years from 2018-2019 for possible UTUC. Data including demographics, imaging and histology were collected from our electronic database. Results: 57 patients had confirmed UTUC, all had CT changes. CTU had an overall positive predictive value (PPV) of 45%. CT findings were divided into: hydronephrosis; filling defect/lesion; urothelial thickening; normal; or other. The PPV was highest for filling defects/lesions at 60%, hydronephrosis was 38%, urothelial thickening was 30%, and other was 33%. Of those with high-grade histology, 61% had evidence of filling defects/lesions and 24% had hydronephrosis. Conclusions: A specific CTU finding of filling defect/lesion in combination with cytology can aid diagnosis and risk stratification of UTUC. This may enable us to reduce use of diagnostic URS, as well as associated risks of intravesical seeding, necessary in the COVID-19 pandemic. With other CTU findings of hydronephrosis or urothelial thickening, a diagnostic URS may be required.